Research on the Impact of Social Media on Consumer Trust - MIRELA-CRISTINA VOICU (Global Economic Observer, 2020)
Trust is one of the most important elements in the process of purchasing and customer loyalty. The benefits of companies that enjoy a high degree of trust are well known. On the other hand, the effects of the lack of confidence are also obvious (unsatisfied consumers, lost sales) and very expensive for the company. Word-of-mouth or "buzz marketing" has gained a great deal of credibility and, implicitly, contributes to increasing the credibility of a company. A positive online presence can add value to the company's products and services, but it can also contribute to increasing the level of trust in its brand. Trust is an important and, at the same time, very complex relationship between the participants in a social network. Trust plays an important role in forming communities within social networks, in assessing information in terms of quality and credibility and decisively determining how information is transmitted across the network. In this context, we intend to bring through the following study more understanding on the extent to which brands have gained consumer confidence through social media.